Virgilianismo y tradición clásica en la Cristíada de Fray Diego de Hojeda - Cristóbal, Vicente (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
Cristíada, by Fray Diego de Hojeda, even though similar in plot to the latin epopee with the same title by Marco Jerónimo Vida, has its generic and structural model in the Aeneid. Virgil’s influence is present in him as far as the structural organization of his subject matter is concerned and in the expansion of argumentative limits through retrospection and exploration. In this expansion lies the main difference between Vida’s epic conception of life and that of Hojeda. Besides, Hojeda’s usage of classical myths is moderate —basically those narrated by Ovid in his Metamorphosis—, rejecting them theologically, although often accepting them as an ornamental ingredient and as a frame for a Christian content.